Rowley Jefferson's Awesome Friendly SPOOKY STORIES - Kinney, Jeff (London, United Kingdom : PUFFIN BOOKS, 2021)
Grab a flashlight, crawl under the covers, and dive into the twisted, unexpectedly hilarious world of Rowley Jefferson's imagination. You'll meet zombies, vampires, ghosts, and much more in these comically terrifying tales. Rowley's spooky stories might leave you laughing, but beware-you could end up sleeping with the lights on! And don't miss Rowley Jefferson's first two awesome friendly books, the instant #1 bestsellers Diary of an Awesome Friendly Kid: Rowley Jefferson's Journal and Rowley Jefferson's Awesome Friendly Adventure!
For ages from 7 to 14 years.
Keywords: Jefferson, Rowley (Fictitious character) -- Juvenile fiction; Ghosts -- Juvenile fiction; Zombies -- Juvenile fiction; Vampires -- Juvenile fiction; Children's stories